Betain and Alcohol-based Deep Eutectic Solvents for Vitexin Extraction from Binahong (Anredera cordifolia) Leaves - Kamarza Wardhani; Elsa A. Krisanti; Geraldi Andika (ASEAN Journal of Chemical Engineering, 2019)
Deep eutectic solvents (DESs) consisting of betaine as the hydrogen donor acceptor and a propanediol or a butanediol as the hydrogen bonding donor were used to extract vitexin from the leaves of Anredera cordifolia (Ten.) Steenis, known in Indonesia as binahong used traditionally to treat wounds. The vitexin extraction yields depend strongly on the molecular structure of the hydrogen bonding donor used and the betaine to alcohol molar ratio. The highest extraction yield of 0.024%, w/w vitexin in binahong leaves, was obtained at room temperature using the mixture of betaine and 1,3-propanediol in 1:4 mole ratio. For each set of DESs having a common HBD, the highest extraction yield was consistently obtained using the DES having betaine to alcohol molar ratio of 1:4. A higher extraction yield of 0.042% was obtained as the extraction temperature was increased to 40 °C. This study shows that DESs made of betaine and polyalcohol are prospective green solvents for extraction of bioactives such as vitexin from plants.